Reading Motivation and Reading Comprehension Ability of The Students at Islamic University of Malang - Nuril Firdaus (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
This article aims at knowing whether there is significant correlation between reading motivation and reading comprehension ability of the third semester students of English Language Teaching Department of University of Islam Malang or not. The research design in this study is quantitative research in the form of correlation design. The subject of this study was 33 students. The researcher developed two research instruments; a questionnaire to measure students’ reading motivation and a test of reading to measure reading comprehension ability. The finding indicated that there was a positive correlation between students’ reading motivation and their reading comprehension ability because the coefficient correlation obtained showed on the table was 0.497. It can be concluded that the correlation between those two variables was on moderate correlation. The coefficient correlation obtained from the computation was significant because r observed was higher than the r critical (0.497 > 0.344).